Tawhid Education in Nadzam Imrithiy: Value Analytic - Muhammad Fodhil; Nurul Ayu Fadilah (SCHOOLAR: Social and Literature Study in Education, 2022)
Pondok pesantren itself is a fairly unique educational institution, not only because of its very long existence, but also because of the methods, culture and networks applied by pesantren. The source of learning used is the yellow book, but the yellow book will not be understood if it has not studied nahwu science. Nadzam Imrithiy by Shaykh Sarafuddin Yahya Al-Imrithiy is one of the books that discusses the science of nahwu containing 254 verses. In nadzam Imrithiy if we examine more deeply it turns out to contain other implied ma'na. The problem that will be discussed this time is the analysis of tawhid education values in nadzam Imrithiy by Syaikh Sarafuddin Yahya Al-Imrithiy. This research is literature with nadzam im rithiy source. The data collected comes from literature, either taken from a book or from a classic yellow book. The values of Tawhid implied in nadzam Imrithiy in the form of believing that there is no god but Allah, only Allah is the place to ask for all things, God can not be seen by the naked eye and always remember God. The value of tawhid education implied in nadzam imrithiy can also be actualized in the education of modern society akhlaq. An example of actualization of no god but Allah is to believe that God governs all that is in this world, so that sustenance,soul mate, lives, fate is arranged by God. His duty is only to strive, as to the fixed outcome of God who decides.